2018
DOI: 10.5812/archcid.61030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Common Molecular Typing Methods for Differentiation of Clostridium difficile Strains in the Study of Hospital Acquired Infections

Abstract: Background: Cross-contamination between patients and the medical imaging device is a worldwide concern. In the current study, the ability of different molecular typing methods for differentiation of Clostridium difficile isolates from patients and medical devices was compared to show their discriminatory power for molecular epidemiological purposes. Methods: A total of 23 C. difficile strains from fresh stool samples of patients subjected to colonoscopy, medical device, and environmental samples of a gastroent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…AZIMIRAD et al showed that PCR-ribotyping gave high discrimination of isolates as PFGE. 38 Accordingly, our results revealed the high discriminatory power of Ribo-2 (DI=0.969). Collier et al reported that PCR-ribotyping was more discriminating than AP-PCR in differentiating 49 P. aeruginosa isolates.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…AZIMIRAD et al showed that PCR-ribotyping gave high discrimination of isolates as PFGE. 38 Accordingly, our results revealed the high discriminatory power of Ribo-2 (DI=0.969). Collier et al reported that PCR-ribotyping was more discriminating than AP-PCR in differentiating 49 P. aeruginosa isolates.…”
Section: Discussionmentioning
confidence: 49%
“…41 Azimirad et al reported that RAPD and ERIC were the best markers in discrimination between C. difficile isolates followed by ribotyping. 38 Besides, ribotyping using Ribo-2 primer was able to Infection and Drug Resistance 2021:14 submit your manuscript | www.dovepress.com DovePress differentiate 75% of isolates followed by ERIC (72.72%) and P-640 primer (70%). Oleńska and Małek found that ERIC-PCR can differentiate 61% of 77 rhizobial strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,19 RAPD fingerprinting can rapidly classify isolates into clusters and the relationship of strains can be determined. 13,19 The RAPD typing showed high discriminatory power and stability for analysis of these strains 29 This method provide reliable results within one or 2 days and allow for early and more precise implementation of infection control measures. 30 Our results strongly suggest that two major RAPD types of C. difficile, isolated from 53.8% (7/13) and 30.8% (4/13) of the patients, were prevalent circulating strains in this studied diabetic population.…”
Section: Discussionmentioning
confidence: 91%